Analytical Corporate Finance - Corelli, Angelo (Springer, 2018)
The book offers an innovative view of the most important areas of study for a newcomer in finance. The book aims to be a guide through the most common and interesting topics of corporate finance, supported by a rich mathematical foundation (from which the term “analytical” in the book title derives). The focus of the book is on the life of the corporation, from the start to the implementation of the most complex projects, and the many different ways financing can be achieved. The new approach proposed by this book involves a strong analytical insight into each topic to give students the tools to really understand the effects of managerial decisions on the life of the corporation. The vision of the book is to offer a guide to corporate finance, capable of helping students and practitioners gain an introduction to the area, as well as giving intermediate users useful insights into and a deeper understanding of the analytics behind each part. The literature of books in corporate finance spans over a wide range of topics and theories. The market is already full of (even good) textbooks facing the issue of the corporation from many points of view. However, the overall offer of corporate finance textbook lacks a rigorous mathematical approach. All these books share the same business-related approach to the topic, focusing more on the corporate aspects rather than the financial substance. The aim of Analytical Corporate Finance is to turn the attention to the financial aspects of the daily life of the corporation, with a robust mathematical setting, and the explanation and derivation of the mostly popular models of the firm. The potential of filling such a niche is evident if one thinks that a course in corporate finance nowadays makes only sense if held at the very beginning of an undergraduate course program in basic finance. There is a demand for high-quality education at master’s level, including a more advanced level of corporate finance courses, which is not fulfilled nowadays and definitely requires a good textbook as a guide for such advanced education in the field.